2018
DOI: 10.1186/s41182-018-0088-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of human respiratory syncytial virus isolated among children with acute respiratory infections in Southern Cameroon during three consecutive epidemic seasons, 2011–2013

Abstract: BackgroundHuman respiratory syncytial virus (HRSV) is the main viral cause of severe lower respiratory tract disease in infants and young children. The aim of this study was to describe for the first time the genetic variability of HRSV in Cameroonian patients living in Yaounde for three consecutive epidemic seasons.MethodsHRSV-positive nasopharyngeal samples detected in children less than 15 years in Yaounde were collected from September 2011 to December 2013. Semi-nested RT-PCR, sequencing, and phylogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
(60 reference statements)
4
6
3
Order By: Relevance
“…These results are similar to those observed in Central African Republic where a prevalence of 3.3% was noticed (24). But they are inferior to the results observed in Cameroon, Nigeria and Gabon where high prevalence rates of RSV were detected in febrile children with 7% in Cameroon (29), 17.7% in Nigeria (30) and 13.5% in Gabon (31). The study performed in Nigeria identified two subtypes of RSV, A and B, with a predominance of the subtype A.…”
Section: Discussioncontrasting
confidence: 79%
“…These results are similar to those observed in Central African Republic where a prevalence of 3.3% was noticed (24). But they are inferior to the results observed in Cameroon, Nigeria and Gabon where high prevalence rates of RSV were detected in febrile children with 7% in Cameroon (29), 17.7% in Nigeria (30) and 13.5% in Gabon (31). The study performed in Nigeria identified two subtypes of RSV, A and B, with a predominance of the subtype A.…”
Section: Discussioncontrasting
confidence: 79%
“…Our study showed an overall prevalence of RSV of 8.0% in the period of 2015 to 2018, with significant annual (6.4%-10.6%) and seasonal (12.7% in rainy season vs 3.0% in dry season) fluctuations. While RSV circulation is high during the winter in temperate climates, 12 a high RSV incidence usually coincides with the rainy season in African countries with a tropical climate, such as in Kenya, 45 Cameroon, 46 Senegal, 34 and Ghana. 47 Also in CAF, most cases were reported in November in a study from 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal swabs were screened to detect respiratory viruses using r-gene commercial duplex AdV/HBoV r-gene™ (Respiratory Multi Well System r-gene™, BioMerieux, Lyon, France) as described elsewhere [ 14 ]. A total of 220 HAdV positive samples were used for further characterization by PCR carried out on hexon gene.…”
Section: Methodsmentioning
confidence: 99%